Kecenderungan Keusahawanan dalam Kalangan Pelajar Sekolah Menengah di Negeri Terengganu (The Intention Entrepreneurship Among Secondary School Students in State of Terengganu) - Ibrahim, Mamat; Wan Mohd Zaifurin, Wan Nawang; Nor Hayati, Sa’at; Sabri, Ahmad (2016)
This study focused on the intention of secondary school students in Terengganu to involved in entrepreneurial that follows the Program Tunas Niaga. The study was conducted using a survey and a quantitative approach. A total of 379 students are members of Program Tunas Niaga in 41 schools randomly selected to answer the questionnaire. The results of this study showed that most of the members of the Program Tunas Niaga very likely to involved in the field of entrepreneurship. Factors such as financial forecasters, role model, personality, barriers, social identity, social norms, knowledge of entrepreneurship and entrepreneurial skills are related intention to involved in the field of entrepreneurship. The study’s findings provide an opportunity for the authorities to increase efforts and changed the approach to bring change to young people to be more likely to involved in the field of entrepreneurship and establish Community Malay Bumiputera Commercial and Business